New Directions in the History of the Jews in the Polish Lands (Academic Studies Press, 2021)
This volume is made up of essays first presented as papers at the conference held in May 2015 at POLIN Museum of the History of Polish Jews in Warsaw. It is divided into two sections. The first deals with museological questions—the voices of the curators, comments on the POLIN museum exhibitions and projects, and discussions on Jewish museums and education. The second examines the current state of the historiography of the Jews on the Polish lands from the first Jewish settlement to the present day.